Battle of Modern Heroes: Healthcare Provider’s Crisis Experiences During Covid-19 Pandemic - Fale, Christabel Evadne P.; Fano, Jiesa Ada Stella D.; Salvador, Ralph Patrick B. (Universitas Pendidikan Indonesia (UPI), 2021)
This paper aimed to describe the coronavirus experiences of the healthcare workers. Numerous studies showed the experiences of healthcare workers during the pandemic, but no information is available on the overall experience. The novelties of this study are the overall experiences and the perception of the healthcare workers during the COVID-19 pandemic. We used a screening tool to determine the suitable participants with an emphasis on the length of their work hours during the pandemic. The interview was conducted online, and the screening tool form was sent to the participant's online messaging account. The result showed the experiences and perspectives of health workers during the pandemic, especially the challenges, difficulties, and changes in work functioning and environment. They also noted the difficulties in their work and personal life. It also showed their weaknesses and threats to their personal life. There were also coping mechanisms and strategies to deal with the challenges. The practitioners during the pandemic have experienced significant difficulties during the pandemic and brought awareness and comprehension to the current situation. This study would not only help the present health response during the pandemic but also any future pandemic to protect the wellbeing of our health workers.